El rol de las TIC en el fortalecimiento del pensamiento crítico de los estudiantes en la era digital - Josa, Jairo Andres (Revista Universitaria de Informática RUNIN, 2024)
The article examines the impact of Information and Communications Technologies (ICT) in promoting critical thinking in education. ICT provides students with access to a wide range of information and interactive tools, fostering critical thinking skills by analysing, evaluating and using data effectively. In addition, ICT facilitates online social interaction, challenging students to express their opinions in an informed way. The article emphasizes the importance of educator guidance in the effective use of ICT and how the digital competence of teachers and students is essential to make the most of their potential.